Lapatinibe: uso em mulheres com câncer de mama metastático: revisão sistemática - Afonso, Sérgio Luís [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Introduction: The five years survival of women with metastatic breast cancer accounts less than 25%. HER2 is an epidermal growth factor; the overexpression of HER2 in the cancer cells decreases survival of these patients Lapatinib is a drug that blocks the intracellular domain of HER2. This blocking could stop or diminish the cell proliferation and improve the survival of these patients. WE performed systematic review and metaanalysis of studies that analyzed the efficacy and safety of lapatinib associated with chemotherapy or hormone therapy for patients with advanced breast cancer that overexpress HER2. Methods: A search of the studies was conducted in MEDLINE, EMBASE, WEB OF SCIENCE, CENTRAL, ICTRP, ClinicalTrials.gov, Cochrane Breast Cancer Group. There were analyzed as the primary endpoint, overall survival (OS), progression-free survival (PFS) and the quality of life, and as secondary endpoints side effects, Results: We identified and assessed 1298 studies. Appling the inclusion criteria were selected five studies. Together these studies included a total of 1127 patients with advanced breast cancer (TNM stage III or IV) with overexpression of HER2. In conclusion it was observed that: for OS lapatinib combined with other drugs decreases the probability of death in 20% (Hazard Ratio 0.80, 95% CI 0.69 to 0.94) p = 0.005. For PFS, lapatinib decreases the probability of tumor progression events or death from any cause in 48% (hazard ratio 0:58, 95% CI 0.67 to 0:50 P < 0,0001. None of the studies analyzed the quality of life. Refers to side effects, patients receiving Lapatinib had more diarrhea (RR 2.5, 95 CI 1.82 to 3.43; P<0.00001; increased risk of cardiac events (RR 1.74, 95% CI 1.02 the 2.99; P<0.04), and higher discontinuation of treatment (RR 4.00, 95% CI 1.44 the 11.17). Conclusion: The use of Lapatinib associated with other drugs decreases the probability of death and increases the likelihood of disease progression free ...

Introdução: O câncer de mama metastático apresenta sobrevida inferior a 25% em cinco anos. A superexpressão do receptor HER2 nas células tumorais destas pacientes piora o prognóstico e diminui ainda mais sobrevida destas pacientes. O lapatinibe é uma droga que bloqueia a porção intracelular do receptor HER2 e esta ação poderia diminuir a proliferação das células neoplásicas diminuindo a progressão do tumor. Foi realizada uma revisão sistemática e metanálise dos estudos que avaliaram a eficácia e segurança do lapatinibe associado à quimioterapia ou terapia hormonal em mulheres com câncer de mama avançado com superexpressõ do HER2. Métodos: A busca dos estudos foi realizada nas bases MEDLINE, EMBASE, WEB OF SCIENCE, CENTRAL, ICTRP, ClinicalTrials.gov, Cochrane Breast Cancer Group. Foram analisados, como desfecho primário, a sobrevida global (SG), a sobrevida livre de progressão (SLP) e a qualidade de vida, e como desfechos secundários os efeitos colaterais relacionados ao tratamento. Resultados: Foram identificados e avaliados 1298 estudos. No final, aplicando os critérios de inclusão, foram selecionados cinco estudos. Juntos, estes estudos totalizaram 1127 pacientes com câncer de mama avançado (TNM estádio III ou IV) com superexpressão de HER2. Em ralação à SG foi observado que Lapatinibe associado a quimioterapia ou terapia hormonal diminui a probabilidade de morte em 20% (Hazard Ratio 0.80, 95% CI 0.69 to 0.94;) p=0,005. Em relação à SLP o Lapatinibe diminui a probabilidade de eventos de progressão tumoral ou morte por qualquer causa em 48% (Hazard Ratio 0.58, 95% CI 0.50 to 0.67 p<0,0001. Nenhum estudo analisou a qualidade de vida. Referente aos efeitos colaterais, os pacientes que receberam Lapatinibe tiveram mais diarreia (RR 2,5, 95 IC 1,82 a 3,43; I2 =86 p <0,00001, aumento de risco de eventos cardíacos (RR 1,74, 95 % IC 1,02 a 2,99; I2 =0% p 0,04), e maior risco de sofrer descontinuidade de...
Lapatinibe: for women with metastatic breast cancer: systematic review
Keywords: Lapatinibe; Mamas - Cancer; Câncer - Tratamento; Metastase; Agentes antineoplasicos; Proteínas quinases ativadas por mitógeno; Lapatinib